Selection of probiotic bacteria from the coral reef and tiger grouper fish (Epinephelus foscoguttatus) farming environment - . Ilmiah; . Sukenda; . Widanarni; Enang Harris (Jurnal Akuakultur Indonesia)
The use of probiotic bacteria is one of the methods in aquaculture to control infectious diseases. This study aims to obtain candidates probiotic bacteria from the coral reef and tiger grouper aquaculture environment (Epinephelus fuscoguttatus). Steps of the study included of: 1) isolation of candidates probiotic bacteria, 2) selection of candidates probiotic bacteria: inhibition test and co-culture methods, 3) enzymatic test, 4) the growth of bacteria test 5) pathogenicity test and 6) the molecular identification of probiotic bacteria. The results showed that of 124 isolates in test zone of inhibition, the four isolates with the widest zone of inhibition of isolate K7, K8, K21, and T4, a total of 51 isolates on co-culture methods, the four isolates were able to suppress the growth of pathogenic Vibrio bacteria, isolates K15, K68, K55, and T36. The results of hydrolyzing the highest protease amylase and lipase enzyme, respectively isolates K15 and T36; isolates T41 and K8; isolates K55 and K68. Candidates probiotic bacteria reached the exponential phase at 16‒18 h. The results of pathogenicity test isolate K7, K8, T36, and T41 provided the highest survival that can be used as candidates probiotics in the tiger grouper.